ANALISIS KETAHANAN KOROSI TIANG INFUS DENGAN PENGGUNAAN BAJA ST 37 YANG DILAPISI NIKEL MELALUI PROSES ELECTROPLATING SEBAGAI ALTERNATIF TERHADAP STAINLESS STEEL 316 - Johanes Darmawan Nainggolan, (2024)
Corrosion resistance of drip poles is a major concern in construction. Although 316 stainless steel has become a common choice, its relatively high price has prompted research into alternatives that are more economical but still have good corrosion resistance. The focus of this research is on iron ST 37 coated with nickel through an electroplating process as an alternative to stainless steel 316. This process is expected to increase the corrosion resistance of iron, making it a competitive solution in drip pole applications. This research aims to carry out an in-depth analysis of the corrosion resistance performance of these two materials, contributing to the selection of optimal construction materials to combat the destructive effects of corrosion on drip poles.